Electronic monitoring and monitoring probation: The case of Ireland. (August 2018) - Moss, Brian
Set against an environment of diverse reforms across the domestic criminal justice system, including new oversight arrangements, the current article considers how probation in Ireland has almost entirely escaped notice. A case for probation oversight is made on the basis of its caseload size but also a decade of unaccounted use of electronic monitoring (EM). Global EM use highlights questions about domestic probation standards, research and planning. Shortcomings within the legislative consultation process around the tool's role, the lack of any evaluation of EM suppliers and increasing focus on data management to date also bolster a case for oversight of Irish probation. A principal issue within this set of challenges for probation is how EM might adjust traditional agency values. Overall, the contention is made that the assumed exceptionalism of Republic of Ireland's criminal justice system, that which acts as a buffer to change, may no longer be valid.